Dietary Acrylamide and the Risks of Developing Cancer: Facts to Ponder - Kumar, Jaya; Das, Srijit; Teoh, Seong Lin (Frontiers in Nutrition, 2018)
Acrylamide (AA) is a water-soluble white crystalline solid commonly used in industries. It was listed as an industrial chemical with potential carcinogenic properties. However to date, AA was used to produce polyacrylamide polymer, which was widely used as a coagulant in water treatment; additives during papermaking; grouting material for dams, tunnels and other underground building constructions. AA in food could be formed during high-temperature cooking via several mechanisms, i.e. formation via acrylic acid which may be derived from the degradation of lipid, carbohydrates or free amino acids; formation via the dehydration/decarboxylation of organic acids (malic acid, lactic acid and citric acid); and direct formation from amino acids. The big debate is whether this compound is toxic to human beings or not. In the present review, we discuss the formation of AA in food products, its consumption and possible link to the development of any cancers. We discuss the body enzymatic influence on AA and mechanism of action of AA on hormone, calcium signaling pathways and cytoskeletal filaments. We also highlight the deleterious effects of AA on nervous system, reproductive system, immune system and the liver. The present and future mitigation strategies are also discussed. The present review on AA may be beneficial for researchers, food industry and also medical personnel.